Bond Behavior of FRP Retrofitted and Old/New Concrete Using Graphene Derivative Modified Epoxy - Kaur, Mandeep (My University, 2024)
Externally bonded fiber-reinforced polymer (EB-FRP) composites have been extensively used to strengthen existing concrete structures; however, debonding failure often prevents the full-strength utilization of FRP. Various studies observe surface preparation techniques and adhesive type as crucial parameters for the effective bonding characteristics and load transfer mechanism between FRP and concrete. Therefore, high-strength epoxy adhesive needs to be developed, which can delay or even eliminate the debonding failure. Past studies show excellent mechanical properties of graphene derivatives modified epoxy composites; nevertheless, its bond behavior as an adhesive between concrete and FRP remains unexplored. The present work uses a bending beam bond test to investigate the bond behavior between CFRP and concrete beams using various nanofiller-modified epoxy at the interface. Three nanofillers, graphite-derived graphene oxide (GO), graphite-derived reduced GO (RGO), and coal-derived GO (CGO), have been incorporated in commercially available epoxy at three different concentrations of 0.05, 0.10, and 0.15 wt% of epoxy resin. Based on interfacial shear strength, failure patterns, CFRP strength utilization, and modified epoxy matrix surface morphology, 0.05 wt% GO-modified epoxy has been observed as the optimum concentration and cost-effective nanofiller. It enhances the interface shear strength by 38% and CFRP strength utilization by 33% compared to the control (without nanofiller) and also changes the failure pattern from adhesive to cohesive. Moreover, the proposed high-strength epoxy resin exhibits more ultimate load value than the control epoxy under varied bond lengths and widths. Further, the GO-modified epoxy composite reduces the effective bond length value due to higher strength and stiffness than the unmodified. Introducing epoxy anchors and grooves between CFRP-concrete interface prolongs the debonding process, which is evident through the formation of the hardening stage in the load-deflection response. The optimized epoxy anchors and grooves configuration shows a 42% and 48% enhancement in the failure load and an 85.7% and 100% increment in the CFRP strain utilization compared with the control specimen due to mechanical interlocking provided by anchors and grooves. Further, GO-modified epoxy in the optimized epoxy groove configuration represents a 59.3% and 114.25% remarkable increase in CFRP’s ultimate load, strain utilization, and complete concrete wedge failure. This significant enhancement is due to the combined effect of mechanical interlocking, friction, and chemical bonding. The microstructure analysis of the GO composite samples confirmed a dense network between the interfaces due to an abundance of oxygen-containing functional groups in GO, strengthening the load transfer path and resulting in improved bond behavior and effective and efficient composite action. Thus, a low-concentrated (0.05 wt%) GO-modified epoxy adhesive can improve CFRP-concrete bond performance in plain and grooved concrete surfaces and delay or eliminate FRP debonding to concrete cohesive failure, allowing better utilization of EB-CFRP in retrofitting or strengthening concrete structures. Retrofitting or strengthening concrete structures also involves adding new concrete to an existing one. The interface of old to new concrete is the weakest plane during retrofitting and repairing of concrete structures, resulting in the interface or adhesive failure of the composite formed. Various surface preparation techniques and adhesives have been used and reported in the literature to improve the bond behavior of concrete-to-concrete interface. Epoxy is a commonly used adhesive to bond existing concrete with new overlay concrete, as it provides high adhesion and chemical resistance; however, inadequate roughness and low epoxy strength negatively affect the epoxied concrete joints, causing poor bonding at the concrete interface. On the other hand, the use of graphene oxide (GO) in epoxy showed significant enhancement in its mechanical properties. Hence, in this work, GO-modified epoxy has been used as an adhesive to improve the bond performance of the interface between existing and new concrete by conducting split tensile, bi-surface shear, and slant shear tests. Simultaneously, a comparison has been carried out with other frequently used surface preparation techniques such as grinding wire brushing (GW), grooves, and adding carbon and glass fiber laminate over the existing concrete with and without neat (plain) epoxy. The GO-modified epoxy has been prepared using three different GO concentrations; out of them, 0.05 by weight % turned out to be the optimum concentration and performed best under all bond strengths, resulting in concrete failure instead of adhesive failure. Furthermore, field emission scanning electron microscopy (FE-SEM) revealed homogeneous dispersion of GO at 0.05% by weight and formation of the bond between GO and cement hydrates with both concrete interfaces. As a result, GO-modified epoxy turned out to be a high-strength adhesive to join existing concrete with fresh overlay concrete for strengthening, retrofitting, and repairing concrete structures, and it shows an effective composite action.
Keywords: Bond behavior; GO-modified epoxy; Old-new concrete; FRP-concrete